Electrical Slow Waves in the Mouse Oviduct Are Dependent upon a Calcium Activated Chloride Conductance Encoded by Tmem16a - Dixon, Rose Ellen (Society for the Study of Reproduction, Inc., 2011)
Myosalpinx contractions are critical for oocyte transport along the oviduct. A specialized population of pacemaker cells—oviduct interstitial cells of Cajal—generate slow waves, the electrical events underlying myosalpinx contractions. The ionic basis of oviduct pacemaker activity is unknown. We examined the role of a new class of Ca(2+)-activated Cl(−) channels (CaCCs)—anoctamin 1, encoded by Tmem16a—in oviduct slow wave generation. RT-PCR revealed the transcriptional expression of Tmem16a-encoded CaCCs in the myosalpinx. Intracellular microelectrode recordings were performed in the presence of two pharmacologically distinct Cl(−) channel antagonists, anthracene-9-carboxylic acid and niflumic acid. Both of these inhibitors caused membrane hyperpolarization, reduced the duration of slow waves, and ultimately inhibited pacemaker activity. Niflumic acid also inhibited propagating calcium waves within the myosalpinx. Slow waves were present at birth in wild-type and heterozygous oviducts but failed to develop by birth in mice homozygous for a null allele of Tmem16a (Tmem16a(tm1Bdh/tm1Bdh)). These data suggest that Tmem16a-encoded CaCCs contribute to membrane potential and are responsible for the upstroke and plateau phases of oviduct slow waves.